Testing the Dynamic Field Theory: Working Memory for Locations Becomes More Spatially Precise Over Development - Schutte, Anne R.; Spencer, John P.; Schöner, Gregor (Child development, 2003)
The dynamic field theory predicts that biases toward remembered locations depend on the separation between targets, and the spatial precision of interactions in working memory that become enhanced over development. This was tested by varying the separation between A and B locations in a sandbox. Children searched for an object 6 times at an A location, followed by 3 trials at a B location. Two- and 4-year-olds', but not 6-year-olds', responses were biased toward A when A and B were 9-in. and 6-in. apart. When A and B were separated by 2 in., however, 4- and 6-year-olds' responses were biased toward A. Thus, the separation at which responses were biased toward A decreased across age groups, supporting the predictions of the theory.